IMPLEMENTASI PENGGUNAAN GOOGLE CLASSROOM PADA PEMBELAJARAN DARING MASA PANDEMI COVID-19 DI KELAS X 1 MADRASAH ALIYAH MUHAMMADIYAH PEKANBARU - Rizky Hardiansah; Ardiah Juita; Agus Prima Aspa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Learning during the covid-19 pandemic is carried out with the Distance Learning (PJJ) system, it aims to break the chain of spread of Covid-19. With this policy, schools implement teaching and learning activities from a distance or online learning. Currently, there are many platforms that can help implement online learning, such as e-learning, Google Classroom, Edmodo, Moodle. During online learning during the Covid-19 pandemic, teachers send themed assignments, send learning videos as learning media to students so that students can immediately understand the material provided by the teacher through Google Classroom. The type used in this research is descriptive. The population in this study is class X 1 Madrasah Aliyah Muhammadiyah Pekanbaru there are 122 people. The researcher took a random sample of 10% of the total 122 students, namely 12 people and a PJOK teacher. The instruments used to collect data are questionnaires for students and interviews for teachers related to the implementation of google classroom. The data analysis technique used is to calculate the questionnaire score on each research indicator. Based on the results of the research, it showed that the implementation of the use of google classroom in online learning during the covid-19 pandemic in class X 1 Madrasah Aliyah Muhammadiyah Pekanbaru was 93.60% classified as very strong.Keywords: Google Classroom, Online Learning During the Covid-19 Pandemic